OPTIMIZATION AND EXPERIMENTAL STUDY ON THE PROCESS PARAMETERS OF HIGH PRESSURE FORMING FORAXLE HOUSING - YANG JingCheng; WANG LiZhong; DAI ChenGuang (Jixie qiangdu)
The optimization of process parameters in the high pressure forming process of bridge shell is studied. According to the structural characteristics of the bridge shell parts,the process of high-pressure forming in the bridge shell is determined;the relationship between the process parameters is determined by artificial neural network modeling,and the influence of each process parameter on the forming results is analyzed by orthogonal test method,and the optimal combination of process parameters is obtained,that is,the axial displacement feed amount is 17 mm,the feed time is 0. 1 s,and the hydraulic loading peak value35. 5 MPa,loading time 0. 25 s. The numerical solution is obtained by substituting the optimized process parameters into the finite element simulation software DYNAFORM, which verifies the correctness of the optimization results of the process parameters. At the same time,the internal high pressure forming test is carried out. The error between the simulation results and the test results of the thickness value of the axial internal high pressure forming is 3. 1%,and the error of the radial results is1. 3%. The agreement between the test results and the simulation results is within a reasonable range.